The role of solid-state fermentation to transform existing waste treatment plants based on composting and anaerobic digestion into modern organic waste-based biorefineries, in the framework of circular bioeconomy - Artola, Adriana; Font, Xavier; Moral-Vico, Javier; Sánchez, Antoni (Frontiers in Chemical Engineering, 2024)
Biorefineries are emerging facilities that are planned to transform existing waste treatment plants based on composting and/or anaerobic digestion into complex installations where biological and physicochemical processes coexist to maximize the recovery of renewable energy and valuable bioproducts. Biorefineries are mainly based on the use of several typologies of organic waste as starting material. This feature, together with the fact that biorefineries are supposed to be carbon neutral, has provoked that two biotechnologies arise as the key to have a successful biorefinery in economic and environmental terms: anaerobic digestion, a consolidated renewable energy provider, and solid-state fermentation, an emerging technology, derived from composting, to act as a supplier of a new generation of biorefinery products that include enzymes, bioplastics, biopesticides, biosurfactants and bioestimulants, among others. This review explores the importance of the role of anaerobic digestion and solid-state fermentation in novel biorefineries, highlighting their obvious advantages and their main challenges, in a specific moment where anaerobic digestion and, in consequence, digestate, are undergoing an exponential increase as a renewable energy source and a predominant organic waste.